A Case Study: The Use Of Translanguaging In The Form Of Lecturer-Directed Translanguaging Of English Department Class Of Mulawarman University - Eirene Letarina; Maria Theodora Ping; Yuni Utami Asih (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2022)
This study aimed to find the translanguaging practice during the teaching and learning process in the online environment class and the factors behind the existence of lecturer‟s translanguaging in the teaching and learning process in the online class. The current study used case study research design under a qualitative approach. This study observed and interviewed a lecturer in English Department at Mulawarman University to collect the data. The data analysis method employed was qualitative content analysis. The current study revealed target language is still the dominant language that appeared in the virtual class. In addition, the lecturer‟s translanguaging appeared in content/language explanation, especially in explaining pronunciation, grammar, vocabulary or difficult terms; drawing attention and comprehension checking; instruction reinforcement. This study also found that translanguaging is used as material sources that created multimodal and multilingual learning. Translanguaging occurred in the virtual class because of four factors: familiarity/friendliness with the students, attitudes and emotions of the speaker, purpose of the message is more important than the language, habit or usual manner of behavior. The current study found that translanguaging has positive values where the lecturer used translanguaging as assistance to make sure the message gets across. Therefore, educators may want to consider allowing the class to translanguage during the teaching and learning process.